Pedagogía activa y su impacto en las competencias emocionales de los estudiantes - García-Cedeño, Gina Aracely; Vélez-Loor, Maira Dolores; Franco-Zambrano, Carmen Narcisa; Ormaza-Bermello, Martha Inés (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
The objective of the research was based on analyzing active pedagogy and its impact on the emotional competencies of high school students in the province of Manabí. It was of a cross-sectional correlational descriptive type with a non-experimental design; the population consisted of 84 high school students. The active pedagogy (PA) is positively correlated in 0.058 with the emotional competences (CE), being necessary to deepen by the teachers. When the research variables are positively related, a favorable perception is conceived by the students about the performance of the teachers in order to promote a comprehensive education where the emotional and academic are combined, promoting a person capable of addressing the different challenges to which he faces due to an assertive management of his behavior.